1983
DOI: 10.1210/jcem-57-2-356
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance in Nonobese Patients with Polycystic Ovarian Disease*

Abstract: To determine whether insulin resistance occurs in polycystic ovarian disease (PCO) in the absence of obesity and acanthosis nigricans, circulating levels of insulin in response to oral glucose administration were measured in 10 nonobese PCO patients without acanthosis nigricans and in 10 normal women matched for weight and height. Mean serum testosterone (T), androstenedione (A), dehydroepiandrosterone (D), D sulfate, and LH levels were significantly elevated in the PCO patients compared to those in control su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
256
2
32

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 690 publications
(307 citation statements)
references
References 17 publications
17
256
2
32
Order By: Relevance
“…(24)(25)(26)(27) Obesity begets insulin resistance, the associated hyperinsulinemia suppresses hepatic production of SHBG, and in turn free plasma testosterone becomes elevated. (28)(29)(30) Women with PCOS have insulin resistance that is more severe than can be accounted for by obesity alone (25,31,32) and this leads to even greater reductions in SHBG and higher androgens. In turn insulin may drive androgen secretion in PCOS, thus causing a feed-forward mechanism promoting hyperandrogenemia.…”
Section: Discussionmentioning
confidence: 99%
“…(24)(25)(26)(27) Obesity begets insulin resistance, the associated hyperinsulinemia suppresses hepatic production of SHBG, and in turn free plasma testosterone becomes elevated. (28)(29)(30) Women with PCOS have insulin resistance that is more severe than can be accounted for by obesity alone (25,31,32) and this leads to even greater reductions in SHBG and higher androgens. In turn insulin may drive androgen secretion in PCOS, thus causing a feed-forward mechanism promoting hyperandrogenemia.…”
Section: Discussionmentioning
confidence: 99%
“…Over the ensuing decades, it became clear that this 'reproductive' syndrome was often accompanied by metabolic features that are a consequence of insulin resistance and hyperinsulinaemia [2][3][4], for example, impairment in oral glucose tolerance, type 2 diabetes [5,6], the metabolic syndrome [7,8] and dyslipidaemia [9,10]. The magnitude of insulin resistance in PCOS is greater than that caused by excess adiposity alone; it is characterised by reduced sensitivity and responsiveness to insulin-mediated glucose utilisation, primarily in the skeletal muscle, adipose tissue and in the liver [11].…”
Section: Introductionmentioning
confidence: 99%
“…As much as 64 % of PCOS patients were found to have insulin resistance that could not be predicted by weight alone [9]. Similarly, strong associations of insulin with various circulating androgens and waist hip ratio (WHR) in PCOS have been reported that were found to be independent of body mass index (BMI) [10][11][12][13].…”
mentioning
confidence: 99%